Kids’ Atlas application to Learn about Geography and Maps - Aljojo, Nahla; Ameen Banjar; Mashael Khayyat; Basma Alharbi; Areej Alshutayri; Amani Jamal; Azida Zainol; Dana Waggas; Ghydaa Saleh; Rahaf Alshehri; Shoroug Aljuaid (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
Geography is the study of local and spatial variations in physical and human events on Earth. Studies of the world's geography have grown together with human developments and revolutions. Atlases often present geographic features and boundaries of areas; an atlas is a compilation of different Earth maps or Earth regions, such as the Middle East, and the continents of Asia, and North America. Most teachers still use classical methods of teaching. Geographical concepts and map-reading skills are the most common aspects of learning that early-stage students find challenging. Hence, the objective of this application is to develop a geography application for children between the ages of 9 and 12 years that would allow them to learn maps. Nowadays, smartphones and mobile apps are drawing closer to becoming acceptable learning tools. To facilitate this, Kids’ Atlas is an android application, the main purpose of which is to help children to learn easily and test their knowledge. The application improves learning through entertainment by adding technologies that will help children to learning geography. It captures their attention to learn by visualizing objects and allows them to interact more effectively than traditional methods teaching by visualizing the 3D items. The application intends to improve the individual’s ability to understand by providing a training section containing simple quizzes, listening/voice recognition capability, and it has the ability to search for a country by voice recognition and zooming for searched country. The methodology involves a set of software development phases, beginning with the planning; analyze data, design, implementation, testing and maintenance phases. The result of this project is a geography learning application that assists children to enjoy learning geography. The result has shown positive indicators that improve children’s ability and knowledge of geography. Learning geography also becomes enjoyable; encouraging and motivating children to continue learning. This project contributes to the growth of education in early childhood, which is essential to shape the nation for the future. Therefore, this project is significant and relevant, as it contributes to the knowledge society for Saudi Arabia.